2023
DOI: 10.1002/pbc.30764
|View full text |Cite
|
Sign up to set email alerts
|

Social participation of school‐aged survivors of pediatric brain tumors: A daily diary report

Mollie Tamboli,
Bethany Means,
Niki Jurbergs
et al.

Abstract: BackgroundDifficulties with social functioning are common among survivors of pediatric brain tumors. Social participation is an understudied measure of social functioning that is associated with emotional health across the lifespan. This paper uses a diary method to assess the social participation of survivors of pediatric brain tumors in middle childhood.ProcedureSurvivors of pediatric brain tumors (N = 47; age 10.6 ± 1.4 years; 51.1% male, 89.4% White) who were 5.3 (SD = 2.4, range: 2–9.9) years post therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…7 Moreover, social information processing-and more specifically, underlying social affective functions-influences social behavior and social adjustment. 14,15 Previous research with SPBT has focused on social attention and face processing as predictors of social impairments, 17,[20][21][22] less and worse peer interactions, 18 and fewer friendships. 23 Taken together, these findings provide a more nuanced picture of the interplay between components of key social affective functions (i.e., social attention and FER) and social impairment in SPBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover, social information processing-and more specifically, underlying social affective functions-influences social behavior and social adjustment. 14,15 Previous research with SPBT has focused on social attention and face processing as predictors of social impairments, 17,[20][21][22] less and worse peer interactions, 18 and fewer friendships. 23 Taken together, these findings provide a more nuanced picture of the interplay between components of key social affective functions (i.e., social attention and FER) and social impairment in SPBT.…”
Section: Discussionmentioning
confidence: 99%
“…17 Evidence indicates that while the frequency and quality of peer interactions are generally low among SPBT, survivors with more positive social experiences demonstrate superior facial expression recognition (FER) abilities. 18 Associations between social attention, FER, and social behaviors have been investigated in children with developmental disorders, namely autism. 19 Research specific to SPBT revealed similar deficits in social attention 16 and FER.…”
Section: Introductionmentioning
confidence: 99%
“…Survivors of pediatric brain tumor (SPBT) experience late effects across many domains [1,2] that pose challenges as they navigate their social milieu [3]. SPBT experience social connectedness difficulties, such as fewer friends and social interactions compared to siblings and other childhood cancer survivors [4,5].…”
mentioning
confidence: 99%